2010
DOI: 10.1080/00343404.2010.486783
|View full text |Cite
|
Sign up to set email alerts
|

Technological Specialization and Variety in Urban Invention

Abstract: O HUallachain B. and Lee D.-S. Technological specialization and variety in urban invention, Regional Studies. Urban economic theory distinguishes between knowledge spillovers that occur within specializations and those that cross technologies. Empirical analysis has sought to gauge their relative strength, but the results are inconclusive. Metropolitan specialization and variety at different aggregation levels of a US patent classification system are assessed using Theil's relative entropy index. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 75 publications
(63 reference statements)
0
14
0
4
Order By: Relevance
“…the importance of agglomeration economies (DUR- ANTON and PUGA, 2004;ELLISON et al, 2010;GLAESER, 1999); . the nature of the local knowledge base (FRENKEN and BOSCHMA, 2007;NEFFKE et al, 2011;Ó HUALLACHÁIN and LEE, 2011); and . the structure of the co-invention network within the city (BETTENCOURT et al, 2007;FLEMING et al, 2007a;LOBO and STRUMSKY, 2008).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…the importance of agglomeration economies (DUR- ANTON and PUGA, 2004;ELLISON et al, 2010;GLAESER, 1999); . the nature of the local knowledge base (FRENKEN and BOSCHMA, 2007;NEFFKE et al, 2011;Ó HUALLACHÁIN and LEE, 2011); and . the structure of the co-invention network within the city (BETTENCOURT et al, 2007;FLEMING et al, 2007a;LOBO and STRUMSKY, 2008).…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…If the cognitive distance between skilled professionals is too wide, the complementary flows of knowledge between them that are needed to propel invention and innovation are unlikely to occur (Nooteboom 2000). Ó hUallacháin and Lee (2011) argued that specialization and variety are not necessarily opposing urban attributes; cities can have both. Beaudry and Schiffauerova's (2009) review of 67 research articles reported an almost even split in support for the merits of industrial specialization and diversity in regional development.…”
Section: Concentration and Colocation Of Inventionsmentioning
confidence: 99%
“…Both specialization and diversification as spillover sources are not necessarily excluding nor antagonistic inside a territory (Duranton & Puga, ; Feldman & Kogler, ; Ó Huallacháin & Lee, ). In agreement with that, Frenken et al () proposed two categories from the concept of diversification: the related variety and the unrelated variety.…”
Section: The Literature Reviewmentioning
confidence: 99%